FACTORS CONTRIBUTING TO POOR INFECTION PREVENTION AMONG HEALTH WORKERS IN NDEJJE HEALTH CENTER IV, WAKISO DISTRICT. A DESCRIPTIVE CROSS-SECTIONAL STUDY. - Najjuma, Asina; Sida, Harrison (Student’s Journal of Health Research Africa, 2023)
Background: The purpose of the study was to find out the factors contributing to poor infection prevention among health workers at Ndejje Health Centre IV, Wakiso District. The objective of the study was to determine the factors contributing to poor infection prevention among health workers at Ndejje health center in Wakiso district. Methodology: This study adopted a cross-sectional study design with a simple random technique as a sampling technique on a sample of 75 respondents 50 were health workers and 25 were patients. Data were collected using questionnaires; data was later analyzed manually systematically by compiling it inform of percentages using micro soft Excel computer program to generate bar graphs, tables, and pie-charts. Results: Findings in health workers-related factors contributing to poor infection prevention were compliance with hand hygiene at 36%, safe infection prevention practices at 36%, attending in-service training on infection prevention bimonthly at 40%, and yearly was 18%. Findings from health-related factors contributing to poor infection prevention were manual cleaning with washer disinfectors 36%, sterilized equipment’s 40%, enough safety boxes and waste bins for sharps and waste disposal 40 Conclusion. Poor compliance to hand hygiene, limited use of personal protective equipment like masks, manual cleaning with fewer washer disinfectants, lack of enough safety boxes and waste bins for disposing of sharps and wastes, limited sterilized equipment, health workers not teaching patient about infection prevention practices are the major factors contributing to poor infection prevention among health workers at Ndejje health center iv, wakes District. Recommendation. The government of Uganda through the Ministry of Health should make sure that sterilized equip- ment, and personal protective equipment.